Iraqi EFL Students’ Ability in Acquiring English Vocabulary by Peer Instruction Technology - Sabeeha Hamza Dehham (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
I Today's learners are driven and inspired by technology in their everyday lives, so it is no longer enough to firmly grip the same old traditional teaching. To raise the learners' awareness of the material being presented, we need to integrate technology and innovation into our teaching routine. Peer Instruction Technology or Smart Phone Responses have gained tremendous worldwide success in teaching as an innovation in the classroom. "This study intends to investigate the effects of clickers on the acquisition of Englis-language vocabulary in the context of Iraq" . The study was using the method of quantitative research. The study samples were randomly selected from the students at the fourth preparatory school. The study adopted pre-test design-post-test. The study results suggested that in both the overall achievement and the acquisition of a vocabulary item,Smart one Responses were better than conventional teaching.